Effects of N-methyl-D-aspartate receptor knockdown and hypoxia/reoxygenation injury on the neuronal proteome and transcriptome - He, Jinting; Chen, Kaili; Sui, Yujie; Yang, Qiwei (Frontiers in Molecular Neuroscience, 2022)
Introduction Brain tissue is extremely sensitive to hypoxia/reoxygenation (H/R) injury, which can easily cause irreversible damage to neurons. H/R injury can induce neuronal apoptosis through glutamate-mediated excitotoxicity. N-methyl-d-aspartate receptor (NMDAR) is one of the main receptors of excitatory glutamate, and blocking NMDAR protects brain tissue from ischemic and hypoxic injury. However, NMDAR hypofunction can also cause psychotic symptoms or cognitive impairment. There is still a lack of systematic research on the changes in the proteome and transcriptome in neuronal cells under conditions of NMDAR hypofunction and H/R injury. Methods We compared the changes in the proteome, transcriptome and lncRNA expression levels in neurons after NMDAR knockdown and H/R by isobaric tags for relative and absolute quantitation (iTRAQ) and RNA sequencing (RNA-Seq). Results The results showed that the proteins Rps9, Rpl18 and Rpl15 and the lncRNAs XLOC_161072 and XLOC_065271 were significantly downregulated after NMDAR knockdown but upregulated after H/R; in contrast, the mRNAs Bank1 and Pcp4l1 and the lncRNAs XLOC_159404 and XLOC_031922 were significantly upregulated after NMDAR knockdown but downregulated after H/R. Discussion In this study, we demonstrated the characterization of protein, mRNA, and lncRNA expression profiles in neurons following NMDAR knockdown and H/R injury. These molecules are involved in multiple biological functions and signaling pathways, and their roles in neurons lacking NMDAR and subjected to H/R injury deserve further study. Additionally, we found that lncRNAs respond fastest to hypoxic stimulation and that Gapdh is not suitable as a reference protein for NMDAR-reduced neuron-related experiments.